Dynamic mechanical properties and the dynamic fragility concept applied to vegetal fiber on vegetal composite materials. (August 2016) - Ornaghi Júnior, Heitor L; Poletto, Matheus; Ornaghi, Felipe G; Zattera, Ademir J; Amico, Sandro C
The dynamic fragility concept has been performed on kenaf and jute composites containing different reinforcement contents. Based on the average relaxation times, we have determined, as a function of the type of reinforcement and fiber content, the dynamic fragility concept of composites manufactured by resin transfer molding. It was constated that for these polymeric composite materials, the glass transition temperature is not a so significant feature to evaluate the characteristic parameters of the Williams–Landel–Ferry and Vogel–Fulcher–Tamman equations. The reason is that for up to 30% reinforcement volume, the glass transition values maintain similar values for these composites, whereas mechanical and dynamical mechanical properties shown an increase in the properties by fiber incorporation. Also, the activation energy as the structural relaxation energy would give a more realistic approach of the results found, following the McKenna supposition.